A Preliminary Study on the Design Method for Large-Diameter Deep-Hole Presplit Blasting and Its Vibration-Isolation Effect - Shuangshuang Xiao; Hongsheng Wang; Guowei Dong (Shock and Vibration)
Presplit blasting can reduce vibration and back impact induced by cast blasting, thus resulting in a smooth bench slope. To design reasonable presplit blasting parameters, this research investigated the formation of presplit faces based on the explosion mechanics and revealed the cracking mechanism of presplit blasting. According to the stress distribution in the vicinity of the blast holes under the action of explosive stress waves and blasting gas, we deduced theoretical formulae for parameters including charge mass in blast holes, hole spacing, and distance from presplit blast holes to cushion holes. On this basis, a method was proposed for the design of large-diameter deep-hole presplit blasting. Field testing was conducted by setting different spacing for presplit blast holes, to monitor the blasting-induced vibration. The results showed that appropriate hole spacing can reduce the particle vibration velocity and the attenuation index of blasting-induced vibration changed slightly while the attenuation coefficient decreased significantly; the formed presplit faces were smooth and had a high half-cast factor. Finally, the reasonable hole spacing for presplit blasting, distance from presplit blast hole to the cushion hole, and the charge mass in blast holes in the Heidaigou open-pit coal mine were determined, respectively.